MENYUSUN KONSEP NOMOR IDENTITAS KOLEKSI MENGGUNAKAN BARCODE BERDASARKAN KARAKTERISTIK PERGURUAN TINGGI - Andi Saputra (Ikatan Pustakawan Indonesia, 2019)
This study aims to formulate the concept identity number of college library collections using barcodes. Identity number (ID) is prepared according to the characteristics of the university. The preparation is guided by the concept used in preparing the student’s identity number (NIM). This research was conducted at Andalas University. The research data was collected using questionnaires, observations, and interviews. Based on the questionnaire results 80% of libraries in Indonesia still use barcodes as a medium to provide collection identity numbers. Some of these libraries do not have written rules for compiling barcode numbers. The ID number compiled in this study contains elements of year, ownership code (faculty), location code where the collection is located, type of collection, the source of acquisition, and index number. The resulting identity number has accommodated all collections in universities, both central library, faculty, and departments. This concept supports the integration process of college library collections and makes it easier to identify collection ownership. Another advantage is that there is no identical identity number for different collections (redundancy) which can cause inconsistencies in the giving of identity. In addition, consideration of the use of various elements in the preparation of this identification number is to facilitate the grouping of collections, as well as the preparation of periodic reports on the library.